Total bacterial count and somatic cell count in refrigerated raw milk stored in communal tanks - Edmar da Costa Alves; Alice Maria Dahmer; Aurélio Ferreira Borges (Brazilian Journal of Food Technology, 2014)
The current industry demand for dairy products with extended shelf life has resulted in new challenges for milk quality maintenance. The processing of milk with high bacterial counts compromises the quality and performance of industrial products. The study aimed to evaluate the total bacteria counts (TBC) and somatic cell count (SCC) in 768 samples of refrigerated raw milk, from 32 communal tanks. Samples were collected in the first quarter of 2010, 2011, 2012 and 2013 and analyzed by the Laboratory of Milk Quality - LQL. Results showed that 62.5%, 37.5%, 15.6% and 27.1% of the means for TBC in 2010, 2011, 2012 and 2013, respectively, were above the values established by legislation. However, we observed a significant reduction in the levels of total bacterial count (TBC) in the studied periods. For somatic cell count, 100% of the means indicated values below 600.000 cells/mL, complying with the actual Brazilian legislation. The values found for the somatic cell count suggests the adoption of effective measures for the sanitary control of the herd. However, the results must be considered with caution as it highlights the need for quality improvements of the raw material until it achieves reliable results effectively.